Agriculture in Korea 2010 - KREI (한국농촌경제연구원, 2010)
Over the past four decades or so, the Republic of Korea has recorded an unprecedented economic growth. However, at the same period, its rapid industrialization and urbanization posed serious challenges to Korean rural areas, including rapid decrease and aging of the farming population and widening income gap between urban and rural areas. In the case of Korean agriculture, the 1950s was a period when the staple grain rice was in short supply as the industry relied on traditional agriculture. However, in the 1960s and 1970s, the industry was able to lay down the ground for supplying the staple grain on its own through technical innovation. In the 1980s and 1990s, the industry saw the birth of modern agriculture, and it is shifting toward an ecofriendly high-tech agriculture in the 2000s. In recent years, Korean agriculture is faced with various problems, such as aging and worsening financial situation of farmers and underdevelopment of farm villages amid increasing opening of the domestic market to foreign agricultural products due to free trade agreements. Korea Rural Economic Institute published Agriculture in Korea in 1999 and Agriculture in Korea 2008 in 2008 with revisions. One of the main purposes of publishing this manuscript series is to explain which roles Korean agriculture has played and how agricultural policies have changed in the economic development process. The publication reviews the current situation and problems in each sector of Korean agriculture and seeks to find their solutions. Also, it aims to help readers outside of Korea to better understand Korean agriculture by introducing and explaining the internal and external roles of the industry and the direction it is headed in the age of globalization. Correct understanding of Korean agriculture will greatly help mitigate frictions with trading partners externally and reach consensus on agricultural policies at home.